Effectivity of Halal Digital Module in Small and Medium Enterprise Practitioner in West Java - Pinandoyo, Dimas Bayu; Jao, Ibrahim (Jurnal Ilmiah Publipreneur, 2024)
This research aimed to measure the effectiveness of the Halal Digital Module in improving the halal knowledge of Small and Medium Enterprise (SME) practitioners in West Java. Ten SME practitioners from Garut, Subang, Cianjur, Bogor, and Depok were involved in the evaluation process. A mixed-method approach was used to analyze the effectiveness. The evaluation was conducted by comparing the pretest and posttest scores of the practitioners and analyzing their feedback. T Test was used to analyze the significance. The results from the pretest and posttest indicated that the Halal Digital Module significantly improved practitioners' knowledge. However, based on the feedback analysis, the module still needs improvement, particularly in the areas of language, the number of questions in the test, and user convenience. The language used in the module was still confusing for some practitioners. The number of questions was excessive and unclear. In terms of convenience, the module performed well on laptops but poorly on Android-based cell phones. It was concluded that Halal Digital Module effectively improve halal knowledge of Small and Medium Enterprise Practitioner, but still need improvement.